Regions of the Russian Arctic Zone: State and Problems at the Beginning of the New Development Stage - Vasilievna Larchenko, Lyubov; Aleksandrovich Kolesnikov, Roman (International Journal of Engineering and Technology, 2018)
In recent years, a new market trading in cryptocurrencies and instruments based on them has been formed. The market of This paper The goal of the study is to analyze the degree of differentiation of the Arctic regions of Russia by the key indicators of socioeconomic development, dependence of their economic development on the raw materials industries, which should be accounted to shape an efficient regional policy by the state and achieve the strategic goals for the reclamation and development of the Russian Arctic zone. The methodology of the study is based on a systematic approach to assessing the socioeconomic and sectoral differentiation of the Arctic regions of Russia. A set of general scientific and special research methods was used. The conducted analysis indicates that all the Arctic regions under study have a narrow raw materials nature of the economy, the sectoral structure is poorly differentiated. The policy of equalizing the per capita income and the cost of living in the Arctic regions with other regions of Russia largely determined the outflow of population from the northern regions. The state regional policy in relation to the Arctic regions should take into account their heterogeneity in order to achieve the results outlined in the strategic documents.Â